The Boundedness of Cauchy Integral Operator on a Domain Having Closed Analytic Boundary - Soykan, Yüksel (Communications in Mathematics and Applications, 2019)
In this paper, we prove that the Cauchy integral operators (or Cauchy transforms) define continuous linear operators on the Smirnov classes for some certain domain with closed analytic boundary.
Keywords: Smirnov classes; Cauchy integral; Cauchy transform; boundedness; Continuity